IJCM_117A: A study to assess the effectiveness of a health educational program on knowledge regarding prevention of Cervical Cancer among young adult female students of Bhopal. - Patne Shailendra Kumar; Pilkhwal Rashmi; Rathore Anshita (Wolters Kluwer Medknow Publications, 2024)
Background: Cervical Cancer is the fourth most common cancer in women & causes significant morbidity and mortality. Every year in India, 122844 women are diagnosed with Cervical Cancer & 67447 die from the disease. Vaccinations to prevent HPV infection have been developed. Awareness regarding Cervical Cancer being a Vaccine Preventable Disease among young adult females is low. Objectives: To determine the awareness of young adult female students regarding Cervical Cancer, its risk factors, screening method & prevention. To assess the construct connection between old and new knowledge by pre & post-test scores. To recommend a health awareness program regarding Cervical Cancer. Methodology: Cross-sectional study of young adult female college students from Commerce, Science and Medical discipline in the city of Bhopal, Sample Size - 387 using Cochran's formula. A pre-validated, pre-tested, close-ended multiple-choice questionnaire on Socio-Demographic information, Domain I i.e. awareness regarding Cervical Cancer including risk factors and symptoms, Domain II i.e. screening & diagnostic and Domain III i.e. vaccination for Cervical Cancer was filled in digital mode before and after the lecture demonstration. Results: The effectiveness of the educational program on most of the components of domain I was found positive but statistically non-significant. In domain II after demonstration, the chi-square test of knowledge on screening technique and diagnostic Pap smear method were found statistically significant and in domain III the chi-square test of knowledge on vaccine for Cervical Cancer was found statistically significant. Conclusion: Prevention and screening measures in young adult female college students were found low and nearly half of the study participants are willing to adopt vaccination and screening program. Teachers can be the best resource persons in dissemination of knowledge in schools and colleges.